Uzayr's donkey: Quran stories for little hearts - Khan, Saniyasnain; Sarkar, Ramen (Goodword Books New Delhi, 2004)
Uzayr's Donkey: Quran Stories for Little Hearts is a captivating children's tale that recounts the story of Prophet Uzayr and his miraculous encounter, teaching young readers valuable lessons about faith, resurrection, and the power of God's will.